2018
DOI: 10.1136/bcr-2018-225097
|View full text |Cite
|
Sign up to set email alerts
|

Rectal mucocele in the anterior wall of the rectum

Abstract: An 84-year-old man presented in 2009 with a sensation of discomfort in his anus, combined with difficulty in urination. He had previously undergone a haemorrhoidectomy in 1964. After examination, he was diagnosed with a rectal mucosal cyst and followed up for observation. In 2015, he presented to our hospital complaining that the cyst was prolapsing from his anus. CT revealed a 48×41 mm cystic mass in the anterior wall of the rectum. Tumour extirpation, via a transanal route, was performed. The postoperative p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Rectal mucoceles are exceedingly rare. Rectal pouch mucoceles following Hartmann’s procedure (proctosigmoidectomy) and rectal wall mucoceles have been known to cause obstruction or compression of other pelvic structures 1 2. To our knowledge and after thorough review of the literature, LBO due to blind colonic limb mucocele of a side-to-end colorectal anastomosis has not been described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rectal mucoceles are exceedingly rare. Rectal pouch mucoceles following Hartmann’s procedure (proctosigmoidectomy) and rectal wall mucoceles have been known to cause obstruction or compression of other pelvic structures 1 2. To our knowledge and after thorough review of the literature, LBO due to blind colonic limb mucocele of a side-to-end colorectal anastomosis has not been described.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic images were essential to narrow down the diagnostic differentials. CT imaging (figure 1) suggested that this could be a rectal wall mucocele—a rare but previously described diagnosis2; however, further imaging was imperative. High-resolution MRI (figure 2) suggested a mucocele of the residual blind colonic loop of a side-to-end anastomosis.…”
Section: Differential Diagnosismentioning
confidence: 92%
See 1 more Smart Citation
“…Entre los factores que pueden contribuir al acúmulo de moco en la luz del muñón rectal después de una cirugía se han descrito: obstrucción luminal, estenosis, aumento del tono anal, así como inflamación, cicatrización y epitelización de la pared intestinal. Dichas condiciones evitan la adecuada eliminación del moco, lo que genera un asa con ambos extremos ocluidos, fomenta la formación de un mucocele, que va a seguir aumentando de tamaño hasta volverse sintomático (2,5).…”
Section: Discussionunclassified
“…El mucocele, desde el punto de vista histológico, consiste en una cavidad con contenido mucinoso rodeada por epitelio o tejido de granulación (1). Se ha descrito en varias localizaciones, pero las más frecuentes son los senos paranasales, el apéndice cecal y la vesícula biliar (2). En una búsqueda realizada en PubMed, en los últimos 20 años se encuentran diez reportes de casos y dos series de casos que describen mucoceles rectales, una con ocho casos y otra con siete casos (3)(4)(5)(6).…”
Section: Introductionunclassified